An Enhanced Approach of Intrusion Avoidance and Privacy Pre-serving for Sharing Healthcare Data on Cloudlet - Karimunnisa, Syed.; Suma Anusha, K (International Journal of Engineering and Technology, 2018)
With the development of clouds and cloudlet technology along with wearable devices, the need for providing security to medical data can be increased. Medical data includes data collection, data storage and data sharing, etc. Traditional healthcare system transmits the medical data to the cloud using sensitive information which causes communication energy consumption. Practically, sharing medical data is a challenging task. Thus in this paper, we propose a novel healthcare system by using the ï¬‚exibility of cloudlet. The operations of cloudlet include privacy protection, data sharing and intrusion detection. In data collection stage, First, the data collected by wearable devices is encrypted using Number Theory Research Unit (NTRU) method and that encrypted data can be transfered to nearby cloudlet. Secondly, we develop a new trust model to help users to select trustable similar patients who want to share stored data in the cloudlet and to communicate with each other about their diseases. Thirdly, we divide usersâ€™ medical data into three parts and give them security which is stored in remote cloud of hospital. Finally, to protect the healthcare system from malicious attacks, we implement a novel collaborative intrusion detection system (IDS) method based on cloudlet mesh, Our experiments proves the effectiveness of the proposed scheme.Â Â